Cryptogenic Multifocal Ulcerous Stenosing Enteritis (CMUSE): A Tale of Three Decades - Singh, Ayaskanta (ACG Case Rep J, 2017)
We present a patient who, over the course of 35 years, presented with repeated episodes of ileus and melena and was misdiagnosed several times, leading to several surgeries. Macroscopic and microscopic features of his resected intestine were compatible with cryptogenic multifocal ulcerous stenosis enteritis (CMUSE), but additional angioectatic lesions were also noted. The patient responded dramatically to hormonal therapy consisting of ethinylestradiol and norethisterone. To our knowledge, this is the first reported case of CMUSE that has shown response to hormonal therapy. We suggest that this is a variant of CMUSE in which vasculopathy plays a role in the pathogenesis.